A guide for easy- and difficult-to-treat hypertension - Schmieder, Roland; Volpe, Massimo; Waeber, Bernard; Ruilope, Luis M. (International Journal of Cardiology, 2014)
Although the blood pressure (BP) of many patients can be controlled using standard combinations, treatment of hypertension frequently represents a clinical challenge to the primary care physician. This article will review best practices for managing patients with easy- and difficult-to-treat hypertension, including preferred antihypertensive combinations, optimizing adherence and persistence, recognizing white-coat hypertension, and intensifying therapy for treatment-resistant patients. Each physician must decide based on his or her own level of experience at what point a patient becomes too challenging and would benefit from referral to a hypertension specialist for more intensive management and to complete the exclusion of secondary forms of arterial hypertension. With intensive pharmacotherapy, many patients with difficult-to-treat hypertension can achieve BP control. If it fails, interventional strategies (e.g., renal denervation) are a valid option to get BP controlled.
EVALuna2:3680